2018
DOI: 10.1007/s10068-018-0413-2
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of propolis phenols by L. plantarum as a strategy for reduction of allergens

Abstract: Propolis is a natural product produced by honeybees. It has antioxidant effects as well as antimicrobial, antiseptic, antibacterial, anti-inflammatory and antimutagenic properties. Except these important healthy properties some cytotoxic effects causing allergies also have been reported. In this study have been evaluated changes of phenolic compounds including allergens molecules found in propolis. Before biotransformation, propolis samples were treated with different solvent (ethanol and polyethylene glycol) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the optimal nanoliposomal formulation of CAPE might reduce any adverse effects associated with the exposure to the free drug such as the reported propolis- and CAPE-induced allergy [ 75 , 76 , 77 ]. It has been shown that the most important allergic molecules in propolis are caffeic acid esters (especially caffeic acid phenyl ester), cinnamic acids and their aromatic esters [ 77 , 78 ]. Future studies will address the possible adverse effects associated with the oral administration of caffeic acid phenethyl ester (CAPE) and CAPE-loaded nanoliposomes (CAPE loaded-NL) in rats without induction of acute pancreatitis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the optimal nanoliposomal formulation of CAPE might reduce any adverse effects associated with the exposure to the free drug such as the reported propolis- and CAPE-induced allergy [ 75 , 76 , 77 ]. It has been shown that the most important allergic molecules in propolis are caffeic acid esters (especially caffeic acid phenyl ester), cinnamic acids and their aromatic esters [ 77 , 78 ]. Future studies will address the possible adverse effects associated with the oral administration of caffeic acid phenethyl ester (CAPE) and CAPE-loaded nanoliposomes (CAPE loaded-NL) in rats without induction of acute pancreatitis.…”
Section: Resultsmentioning
confidence: 99%